A Management of 66 Years Old Women With Gout Artritis, Type II Diabetes Melitus, and Hypertension Using a Family Medicine Approach in Rajabasa Indah Community Health Center Area - Revika Gina Luthfiya; Nusadewiarti, Azelia (Medula, 2025)
Gout Arthritis is a chronic progressive non-communicable disease caused by monosodium urate (MSU) crystal deposits. The prevalence of gout in Indonesia is the highest among other Asian countries. Diabetes and Hypertension are non-communicable diseases that occur in the world. Diabetes mellitus (DM) is a metabolic disease caused by impaired insulin secretion or insulin function. Type 2 diabetes mellitus is the leading cause of death in the world. The prevalence of type 2 DM sufferers according to the 2018 Riskesdas is 8.5%. Hypertension is a silent killer disease, according to the 2018 Riskesdas the prevalence of hypertension was 34.1%, an increase compared to 2013 which was 25.8%. Hypertension is a condition when blood vessel pressure is more than 140/90 mmHg. According to WHO 1.28 billion adults aged 30-79 years worldwide suffer from Hypertension. The diagnosis of Gout arthritis, Diabetes mellitus, and Hypertension is made based on clinical and supporting findings. A holistic approach based on family physicians was implemented through drug and non-drug interventions, including nutrition education, physical exercise, and family counseling in three home visits. Evaluation showed a decrease in uric acid levels, blood sugar, and improvement in blood pressure, as well as an increase in understanding and changes in patient behavior related to disease management. Patients began to implement a healthy lifestyle, such as regular exercise and food recording. An evidence-based medicine approach with family support has been shown to be effective in improving disease control and patient quality of life.